Linguistic Variation and Change in the Portuguese of São Tomé - Bouchard, Marie-Eve (Journal of portuguese linguistics, 2018)
Bouchard presents a dissertation focusing on the variety of Portuguese spoken in Sao Tome, the capital of Sao Tome and Principe. The objective of the study is to investigate the emergence of a Santomean variety of Portuguese, with special reference to rhotics and subject pronoun expression, and to contrast Santomean Portuguese with other varieties of Portuguese. In a larger context, it also explores the social and ideological phenomena that explain the linguistic choices, linguistic change, and language shift in Sao Tome and Principe.